Penerapan Teknik Hard dan Soft Switching pada Motor Switched Reluctance 3 Fasa Menggunakan Psim - Jumardi; Salechan (Politeknosains, 2017)
Classic converter is a series of power converters required to activate and deactivate the motor SRM (switched reluctance motor) which consists of two switches (IGBT) and two diode flywhell for each phase Before making the appliance power converters are real, necessary modeling to know and understand the behavior and the interaction between these converters with a motor. In this study, classic converter modeled with PSIM software to recognize performance by applying the hard and soft switching techniques. Mechanical hard switching is a condition where the second IGBT current on and off is made in the same time, while the soft switching technique is a condition in which the second working IGBT current on and off is made in different time. In order to implement these two techniques required angle and angle on the pulse. On the corner is a corner to produce forward rotation, the magnitude of 900. The pulse angle is the angle to produce the desired rotation and torque (set pulse width), the magnitude of 00 - 1200. angle and angle on a series of pulses inserted into the controller to turn on and off a series of classic converter which supplies the source voltage to the stator coil. Mechanical hard switching produce rotation, minimum torque, which is greater than the voltage soft switching techniques. Soft switching technique produces motor current and losses in semiconductor that is larger than the hard switching techniques. Mechanical hard switching. generates maximum torque similar to a soft switching technique (1.213 Nm and 1.216 Nm).